Analysis Dissenting Opinion and Concurring Opinion in Decision MK No.90/PUU-XXI/2023 Perspective Siyasah Qadhaiyyah - Muhammad Farhan; Khalid (Dinasti Research, 2025)
In the Constitutional Court Decision NO. 90/PUU-XXI/2023, which discusses the age limit for presidential and vice-presidential candidates, there are several discrepancies in the trial process. This is due to two constitutional judges presenting different arguments but reaching the same conclusion (Concurring Opinion) and four constitutional judges expressing differing opinions (Dissenting Opinion). There is an anomaly where the two judges with Concurring Opinions should be more appropriately categorized under Dissenting Opinions. If we examine the reasoning of the two judges with Concurring Opinions, it can be assessed that their arguments lean more towards the Dissenting Opinion, but their opinions shifted to the part that granted the request. The problem formulation to be discussed includes, first, how to analyze the Dissenting Opinion and Concurring Opinion of the judges in the Constitutional Court Decision No. 90/PUU-XXI/2023, which reflects differing views among the judges regarding the substance of the case examined, and second, how to view and interpret the Constitutional Court Decision No. 90/PUU-XXI/2023 regarding the judges' opinions in the trial from the perspective of Siyasah Qadhaiyyah, such as the principles of public policy in Islam that are oriented towards the welfare of the community.